Kinetic adjustment of serial reactions in the acid hydrolysis of cellulose and hemicellulose from rice husk - Sigüencia Avila, Jorge Marcelo; Soler Herrero, Jaime; Menéndez Sastre, Miguel (Jornada de Jóvenes Investigadores del I3A, 2019)
The kinetic constants for the hydrolysis process of rice husk have been determined with experiments at different operating conditions